A Study of Papuan Children's Preferences for Cross-Cultural Narratives: Understanding Early Literacy Engagement - Sri Winarsih; Rusli (Universitas Islam Negeri Palopo, 2025)
This study investigates the narrative literacy preferences of Indigenous Papuan children in the Bevak Pintar Community in Merauke. Recognizing the need for culturally diverse and contextually relevant reading materials, the research employs a descriptive qualitative design using observation, semi-structured interviews, and closed-ended questionnaires. Data were analyzed by classifying narrative types according to themes, character representation, and cultural values. Findings indicate four dominant preferences: (1) Papuan folktales highlighting local wisdom and identity; (2) cross-cultural friendship stories depicting interactions across diverse backgrounds; (3) inspirational global children’s stories presenting resilience and social solidarity; and (4) fantasy narratives blending Papuan mythology with broader imaginative elements. Children favored stories featuring peers with relatable experiences and clear, engaging visual elements. This study contributes novel evidence on Papuan children’s cross-cultural narrative interests and offers implications for developing culturally responsive literacy materials and early-grade curriculum design.